PROSES PEMBERIAN IZIN USAHA MIKRO, KECIL, DAN MENENGAH DI KECAMATAN SENAPELAN DAN KECAMATAN LIMAPULUH KOTA PEKANBARU TAHUN 2017 - Naldi Guswara; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Licensing for Micro, Small and Medium Enterprises is carried out by the implementation of one-stop integrated services organized by the Government and Local Government. Micro and small business licenses hereinafter referred to as IUMK shall be a sign of legality to a person or business actor / activity in the form of a small and micro enterprise license in the form of one sheet. And the purpose of the IUMK is to provide legal certainty and means of empowerment for Micro and Small Business Actor (PUMK) in developing its business. Observing the field data found as many as 13,687 micro, small and medium enterprises in Pekanbaru City only 1,102 licensed businesses. Most entrepreneurs have Micro, Small and Medium Business License in Senapelan Sub-district, which is 301 businesses, while at least have Micro, Small and Medium Business License in Kecamatan Limapuluh that is 21 business. The problem in this research is how the process of granting micro, small and medium business permit in Senapelan and Kecamatan Limapuluh Kota Pekanbaru subdistrict in 2017 and what are the factors that hinder it. The purpose of this research is to know the process of granting of micro, small and medium business permit in Senapelan and Kecamatan Limapuluh Kota Pekanbaru subdistrict in 2017 and the factors that hinder it.In this research, the researcher uses descriptive research type with qualitative method approach. This research is located in District of Senapelan and Kecamatan Limapuluh Kota Pekanbaru. For informant research using purposive sampling technique. Data collection techniques used are observation, interview and documentation. To examine the problem the authors perform data analysis using qualitative descriptive method.The results of this study can be concluded that the process of granting licenses micro, small, and Medium Enterprises In District Senapelan and Kecamatan Limapuluh Pekanbaru City in 2017 is running well enough. The success of the process of granting micro, small and medium business licenses with due consideration of mechanism by Kecamatan Senapelan Pekanbaru realized the importance of business licensing process improvement, and Kecamatan Limapuluh Kota Pekanbaru by trying to realize effective business licensing mechanism.Keywords: Process, Licensing.